Vertragsmanagement in Molkereien nach Auslaufen der Milchquotenregelung; Contract Management of Dairies after Phasing out of the Milk Quota - Stephanie Schlecht; Nina Steffen; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2013)
– As a result of the expiry of the EU milk quota on April 1st 2015, raw milk procurement in the German dairy industry faces major changes. Delivery contracts between dairy farmers and milk processors are the basic coordination mechanism of business relationships and need thus to be adapted to the altered market situation. We analyze empirically the farmers' preferences for different stipulations (pricing systems, volume control and the duration of the contract) and test if their attitudes towards contracting in general have an influence on contract choice. Results illustrate that farmer-suppliers' preference for cooperatives, trust in prices and a focus on entrepreneurial goals increases the likelihood to choose the classical cooperative contract. Based on the results, we discuss implications for contract management in dairies.
Keywords: 330